(untitled) (Annals of Medical Research, 2023)
Aim: The aim of this study was to evaluate the effects of different surface conditioning method combinations on the shear strength of orthodontic brackets bonded various temporary crown materials used in computer aided design and computer aided manufacturing systems. Materials and Methods: 100 polymethyl methacrylate, 100 bis-acrylic composite and 100 polyetherketoneketone surfaces were prepared from provisional temporary crown blocks. Five different conditioning protocols (etching with 9.6 % hydrofluoric acid, sandblasting with 50 μm Al2O3 particles, roughening with ultrafine diamond bur, Er,Cr:YSGG laser irradiating and priming with methylmethacrylate monomer were applied to the surfaces for each material group. Shear test was performed to half of the bonded samples after 24 hours while the other half 14 days later. The share strengths of the bonded brackets were measured in Newton and Megapascals. Results: In all material groups, the highest share strength values were found in samples sandblasted with Al2O3 particles. For bis-acrylic composite and polymethyl methacrylate groups, the lowest bond strength value were found in samples irradiated with Er,Cr:YSGG laser. Conclusion: The shear bond strengths of the orthodontic brackets bonded to the temporary crown materials produced in CAD/CAM systems vary according to the structure of the material and surface conditioning processes.